Influence of Institutional Factors on Student Satisfaction With Online Classes During The Covid-19 Pandemic - Irena TADIC; Irena PANDZA BAJS; Sinisa OPIC (Communications of International Proceedings, 2022)
Online teaching has been used on a smaller scale in universities around the world for many years, but due to circumstances caused by the Covid-19 pandemic, all classes in 2020 had to switch to online, which emerged as the best option for continuous and effective maintenance of teaching at all levels of education. Given the speed and unpreparedness of educational systems for this form of teaching, the question has arised on success and satisfaction of pupils and students with online teaching during the Covid 19 pandemic. Accordingly, this research analyzes student satisfaction with online classes during the Covid 19 pandemic as one of the main components in the process of identifying success factors in online classes at the University. As part of the empirical part of the paper, a study was conducted on the impact of institutional factors on University of Zagreb students' satisfaction with online teaching during the Covid-19 pandemic. Research results indicate that students are generally satisfied with online classes, and accept this way of learning and teaching. In the context of institutional factors, research has shown that organization and elements of classes, together with speed of feedback, were the factors that had greatest impact on student satisfaction with online classes during the Covid 19 pandemic.
Keywords: students satisfaction; online classes; Covid – 19 pandemic